Optimal duration of anticoagulation - Prandoni, Paolo; Barbar, Sofia; Milan, Marta; Campello, Elena; Spiezia, Luca; Piovella, Chiara; Pesavento, Raffaele (Thrombosis and Haemostasis, 2015)
Once anticoagulation is stopped, the risk of recurrent venous thromboembolism (VTE) over years after a first episode is consistently around 30%. This risk is higher in patients with unprovoked than in those with (transient) provoked VTE, and among the latter in patients with medical than in those with surgical risk factors. Baseline parameters that have been found to be related to the risk of recurrent VTE are the proximal location of deep-vein thrombosis, obesity, old age, male sex and non-0 blood group, whereas the role of inherited thrombophilia is controversial. The persistence of residual vein thrombosis at ultrasound assessment has consistently been shown to increase the risk, as do persistently high values of D-dimer and the early development of the post-thrombotic syndrome. Although the latest international guidelines suggest indefinite anticoagulation for most patients with the first episode of unprovoked VTE, strategies that incorporate the assessment of residual vein thrombosis and D-dimer have the potential to identify subjects in whom anticoagulation can be safely discontinued. Moreover, new opportunities are offered by a few emerging anti-Xa and anti-IIa oral compounds, which are likely to induce fewer haemorrhagic complications than vitamin K antagonists while preserving the same effectiveness; and by low-dose aspirin, which has the potential to prevent the occurrence of both venous and arterial thrombotic events.
Keywords: Venous thromboembolism; deep venous thrombosis; pulmonary embolism; anticoagulation; thrombophilia; residual thrombosis; ultrasonography